2008
DOI: 10.1523/jneurosci.2659-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cognitive Functioning in Symptomatic Huntington's Disease As Revealed by Behavioral and Event-Related Potential Indices of Auditory Sensory Memory and Attention

Abstract: Cognitive functions are thought to deteriorate globally in late stages of various neurodegenerative disorders. Here we describe that this general assumption is not justified and fails in Huntington's disease (HD). Presymptomatic gene mutation carriers (pHDs) and healthy controls performed worse compared with symptomatic HDs in an auditory signal detection task. During task performance, behavioral data and event-related potentials (ERPs) [i.e., MMN (mismatch negativity), P3a, and RON (reorienting negativity)] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 41 publications
(54 reference statements)
8
49
1
1
Order By: Relevance
“…Thresholds measured by click ABR analysis were significantly higher in Hdh (CAG)150 mice than in WT mice ( Figure 1F). ABR thresholds for tone bursts of 4,8,16, and 32 kHz of Hdh (CAG)150 mice also revealed a trend toward deteriorated hearing ability and a significant elevation of the threshold levels at 4 and 8 kHz (P < 0.01 and P < 0.05, respectively). Because of the late onset of symptoms in Hdh (CAG)150 mice, the WT controls (age matched at 15 months) had developed presbycusis at 16 and 32 kHz.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…Thresholds measured by click ABR analysis were significantly higher in Hdh (CAG)150 mice than in WT mice ( Figure 1F). ABR thresholds for tone bursts of 4,8,16, and 32 kHz of Hdh (CAG)150 mice also revealed a trend toward deteriorated hearing ability and a significant elevation of the threshold levels at 4 and 8 kHz (P < 0.01 and P < 0.05, respectively). Because of the late onset of symptoms in Hdh (CAG)150 mice, the WT controls (age matched at 15 months) had developed presbycusis at 16 and 32 kHz.…”
Section: Figurementioning
confidence: 89%
“…PolyQ-expanded mutant Htt forms nuclear and neutrophil aggregates and preferentially affects the striatum and the cortex in the brain and several peripheral tissues (2,3). Recent studies demonstrate that late-stage HD patients have abnormal auditory sensory memory and that auditory processing is altered in HD patients (4,5). Nevertheless, the peripheral auditory functions of HD patients have not yet been thoroughly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Here visual input likely modulates basal ganglia networks that are important for action selection processes (e.g., Beste et al 2010a,c;Redgrave and Gurney 2006). This may have important consequences for the process of action selection in the basal ganglia that operates as a "winnertake-all network" (WTA) (Beste et al 2007(Beste et al , 2008bPlenz 2003;Redgrave et al 1999;Wild-Wall et al 2008). Due to the WTA network, only the action is selected that produces strongest activation and is presented to the basal ganglia by cortical afferents.…”
Section: Attentional Processing and Action Selectionmentioning
confidence: 99%
“…A few studies indicated specific changes in amplitude and latency of P300 in clinically isolated syndrome and multiple sclerosis, as well as effects of interferon beta-1b to cognitive functions, even the P300 characteristics (21)(22)(23). Some studies indicated changes in P300 characteristics in patients with Parkinson's disease (the changes correlated with the degree of the disease determined according to the Hoehn and Yahr scale), growth hormone deficiency, Huntington's disease, Tourette syndrome, and narcolepsy (2,9,(24)(25)(26)(27). Changes of P300 characteristics, lowered amplitude, and extended latency have also been noticed in schizophrenia (28)(29)(30)(31)(32)(33)(34)(35)(36), post-traumatic stress disorder (36,37,40), endogenous psychoses (38)(39)(40)(41), panic disorder (42)(43)(44)(45), and depressive patients (46,47).…”
Section: Review Of Literaturementioning
confidence: 99%
“…ERP components such as auditory evoked P300, associated with cognitive processes (i.e., attention and orientation), show low amplitude and long latency in acute and chronic diseases (4)(5)(6). P300 testing is an unbiased and non-invasive method, standardized for assessing cognitive processes (7)(8)(9)(10). We have reviewed the existing literature in this field to better understand the role of P300 testing in diagnostics of different diseases.…”
Section: Introductionmentioning
confidence: 99%